Basic single-event mechanisms in Ge-based nanoelectronics subjected to terrestrial atmospheric neutrons. (November 2021) - Munteanu, D.; Moindjie, S.; Autran, J.L.
Abstract: Germanium is potentially candidate to replace silicon in ultra-scaled transistors. This work analyses the radiation response of germanium in thin layer subjected to atmospheric neutrons simulated with Geant4 and quantifies the underlying mechanisms potentially responsible of single event effects in Ge-based CMOS technologies. From this analysis of interactions at material-level, reliability assessments for Ge-based nanoelectronics are tentatively deduced for technological nodes ranging from 180 nm to 5 nm in terms of nature and number of nuclear events susceptible to upset a SRAM memory cell. Finally, first soft error rate projections are performed for germanium SRAMs in 130, 65 and 40 nm based on a simulation methodology previously developed and fully validated on silicon memories also characterized by real-time experiments. Highlights: Interactions of atmospheric neutrons with germanium thin film materials is investigated using Geant4 simulations Secondaries produced in Ge material are characterized in terms of energy, linear energy transfer and range distributions Low energy recoils are much more important in Ge than in Si, doubling the number of products between 180 and 5 nm nodes SER values of Ge-SRAMs at 130, 65 and 40 nm are found in the same order of magnitude than the ones related to Si-SRAMs.